2015
DOI: 10.4103/0970-2113.156222
|View full text |Cite
|
Sign up to set email alerts
|

A disintegrin and metalloprotease 33 polymorphism association with COPD in long-term tobacco smokers of the ethnic Kashmiri population of India

Abstract: Background:Chronic obstructive pulmonary disease (COPD) is characterized by an interaction of various environmental influences especially cigarette smoking and genetic determinants. The prevalence of this disease is ever increasing and characterization of the genetic determinants of the disease has been undertaken globally. The ‘A disintegrin and metalloprotease 33’ (ADAM 33) gene is one candidate gene that has been studied.Objective:Our objective was to investigate whether single nucleotide polymorphisms in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Polymorphisms in IL-6 [68], IL-4 [69], high-affinity IgE receptor [70], IL-4R [71], disintegrin and metalloproteinase 33 [72], and IL-13 [73] have been associated with epithelial dismantling and malfunctioning, especially in the context of asthma and chronic obstructive pulmonary disease [74,75]. In this sense, a high level of IL-13 in asthmatic patients has been involved in wall remodeling processes [76,77].…”
Section: Airway Epithelium As a Key Player In Orchestrating The Allermentioning
confidence: 99%
“…Polymorphisms in IL-6 [68], IL-4 [69], high-affinity IgE receptor [70], IL-4R [71], disintegrin and metalloproteinase 33 [72], and IL-13 [73] have been associated with epithelial dismantling and malfunctioning, especially in the context of asthma and chronic obstructive pulmonary disease [74,75]. In this sense, a high level of IL-13 in asthmatic patients has been involved in wall remodeling processes [76,77].…”
Section: Airway Epithelium As a Key Player In Orchestrating The Allermentioning
confidence: 99%
“…Nevertheless, COPD genetic profiling use in the clinic is current limited to find out Alpha-1 antitrypsin deficiency (7,8) . Furthermore, the relationship between A disintegrin and metalloprotease 33 (ADAM33) polymorphisms and COPD has been reported by other researchers (9)(10)(11) .…”
Section: Introductionmentioning
confidence: 73%
“…In the Kashmiri population of India, ADAM33 gene polymorphism in three SNPs (T1, T2, and Q-1) were obviously associated with COPD (11) . The results of present study showed that the similarities of findings in T1 and T2, but Q-1 was different.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation